MOTIVASI BELAJAR DALAM FILM ANIMASI NARUTO UZUMAKI (Studi Perspektif Psikologi Belajar) - Rofi’ah, Siti; Sari, Siti Destia Retno (Al Tadib : Jurnal Ilmu Pendidikan, 2016)
This article is aimed at describing the motivation inspired by Japanese animation Uzumaki Naruto, the hero of Japanese animation series that became a favorite both from the children to adults. Naruto is a figure described as a child who came from the village of Konoha, the Fire Nation who lived alone and did not know her father was then known that the father is the 4th Hokage Minato and his mother Ushina Uzumaki is the owner Kyūbi. Naruto grows into a man who had a vision for the future that is becoming Hokage so that people recognize its existence when it was shunned because kyubi society that is in itself cause damage to the village of Konoha. The vision makes Naruto gets better learning. Therefore, the result is,: 1. Motivation is the impetus, the will, or will power to awaken and direct the behavior of individuals, intrinsic and extrinsic motivation. 2. Learning is a relatively permanent change in behavior as a result of their experience and training 3. Naruto movie that is associated with learning motivation of extrinsic motivation, self-esteem and also the motive actualization. Naruto is also associated with learning, because in it, there is a correlation between the activity of learning, elements of learning, and learning characteristics, as well. Keyword: Motivation, Naruto Uzumaki, Psychology